Analysis of volatile compounds and antioxidant activity of Colombian ginger (Zingiber officinale) essential oil obtained by hydrohydraulic distillation assisted by microwave radiation - Tapiero-Cuellar, Jose Libardo; Salamanca-Grosso, Guillermo; Benitez, Maria Andrea (Revista Colombiana de Investigaciones Agroindustriales, 2021)
The (Zingiber officinale) is a plant of the zingiberáceas family, its rhizome is widely used in gastronomy for its pungent aroma and flavor. Essential oils (EO) are natural compounds; they have 25 to 70 components with different concentrations. Α-Zingiberene and α-Felandrene are the main components with volumes between 20% and 70%. For the extraction of the AE samples from 10 Colombian geographical locations were used, obtained by microwave radiated hydrodistillation (MWHD) and stored at 4°C in amber vials. 50 µL of EA and 1.0 µL of (n-tetradecane) internal standard were dissolved in dichloromethane to a final volume of 1.0 mL. The EO components were performed on a triple quadruple mass detector gas chromatograph (BRUKER 450GC-320). For its antioxidant activity (AA) the methodology of Prior for DPPH* and ABTS+ was used. The extractions showed a yield between 0.053 and 0.109 percent; and 300 g of sample at 700 watts and 40 minutes of process were used. The chromatographic profile showed 43 components referring to ketones, alcohols, cyclic ethers, aldehydes and 23 hydrocarbons, with α-Zingiberene being the majority, considered as a molecular marker of this EO. The AA presents significant differences between the samples evaluated for the localities studied.